The Quality of English Final Test at the Second Semester of Third Grade Students of SMAN 1 Pagaran in Academic Year 2016/2017 - Horhon Lumbantoruan; Sri Minda Murni; Isli Iriani Indiah Pane (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
The objective of this study is to find out the quality of the English final test designed for the second semester of third grade students of SMAN 1 Pagaran in academic year 2016/2017. It describes whether or not the test items have good characteristic of test in terms of validity, reliability, difficulty level, and discriminating power. The test consists of 35 items multiple choice forms. The research design uses in this study was Descriptive Qualitative Research. To find out the discriminating power of the test, the writer chose the top 31% for the upper group and top 31% for the lower group. The result of this study shows that there are 18 (51%) acceptable items to meet the criteria of validity and 17 items (49%) is Invalid. The test is reliable since has 0.676 the level of validity. The test has unacceptable index of difficulty since has 15 items (43%) too difficult and are only 5 items (14%) easy items. Whereas for discriminating power index, the writer found there are 7 (20%) has negative result of the point have to be discard, 6 (17%) poor items, 8 (22%) satisfactory items, 13 (38%) good items, and 1 (3 %) excellent item. In conclusion, English final test designed for the second semester of third grade students of SMAN 1 Pagaran in academic year 2016/2017 does not meet the criteria of effective and acceptable test.Keywords:  Validity, Reliability, Level of Difficulty, Discrimination Power